(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2019)
Step-by-step home life does not end with divorce. Divorce of joint property in marriage is another problem that arises after divorce. Joint property is the property or income of the wealth acquired during the marriage. Although the property is derived only from the husband’s work, the wife still owns the property. Thus, joint property includes property derived from the efforts of the husband and wife or the efforts of one of them in another arrangement in the marriage agreement, in the event of divorce then both the wife and the husband are entitled to half (both) of the joint property. between the ex-husband and the wife in the sharing of the joint property.